3(2z-2)-3(5-3z)=3

Simple and best practice solution for 3(2z-2)-3(5-3z)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2z-2)-3(5-3z)=3 equation:


Simplifying
3(2z + -2) + -3(5 + -3z) = 3

Reorder the terms:
3(-2 + 2z) + -3(5 + -3z) = 3
(-2 * 3 + 2z * 3) + -3(5 + -3z) = 3
(-6 + 6z) + -3(5 + -3z) = 3
-6 + 6z + (5 * -3 + -3z * -3) = 3
-6 + 6z + (-15 + 9z) = 3

Reorder the terms:
-6 + -15 + 6z + 9z = 3

Combine like terms: -6 + -15 = -21
-21 + 6z + 9z = 3

Combine like terms: 6z + 9z = 15z
-21 + 15z = 3

Solving
-21 + 15z = 3

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 21 + 15z = 3 + 21

Combine like terms: -21 + 21 = 0
0 + 15z = 3 + 21
15z = 3 + 21

Combine like terms: 3 + 21 = 24
15z = 24

Divide each side by '15'.
z = 1.6

Simplifying
z = 1.6

See similar equations:

| 3y/4=0.6 | | 60-3(E-5)= | | -3x+8x^2+1=0 | | 3(r-4)=3 | | -2b=10-8.58 | | 5h+9=4h+1 | | 3L+22=9l-20 | | 6-3f=18 | | 1.4t-12=-0.6t | | 1.4t-12=4x+23 | | x^2-2bx+a^2=0 | | 500+45(5)=y | | 500+45x=y | | 0.4xsquared-40x+360=0 | | z^2+4iz+5=0 | | x+5y/x | | 3(x-7)-4(x+2)=20 | | (x+5y)/x | | 4x-1=64 | | 7/11=x/45 | | 5x+0.9= | | 7x+0.2= | | 1/3(7x-1)=1/4 | | 81=9a | | 182/7+(5*11)=9a | | 12+144+20+6/7+(5*11)=9a | | 401.28+.2x=x | | -2+128=10 | | 5x-7=2x+12 | | 5x-14=x+14 | | x+13=39 | | 1/8x=8 |

Equations solver categories